THE OTHER SIDE OF THE ADVERTISING TAX ( Study Case in District Demak ) - Muhammad Fauzan; MG. Kentris Indarti; Nungki Pradita (Faculty of Economic and Business Universitas STIKUBANK, 2022)
The purpose of the research is to optimize the contribution of billboard tax as a source of local funds and minimize the potential for lost billboard tax (EOL) in Demak Regency. This type of research is an explantative study that aims to find an explanation of the phenomenon of not optimal Reklame Tax as a Source of Regional funds. The object of this research is The Billboard Tax in Demak Regency. The sub-districts selected as research samples are potential sub-districts for billboards in the sense of easy access from various corners, crowded centers and or city centers including (1) Demak kecematan, (2) Guntur subdistrict, (3) Karangawen subdistrict, and (4) Mranggen subdistrict. These four subdistricts are used as analysis bases to then be generalized as a representation of Demak Regency. The data source is obtained by documentary studies, interviews with relevant officials, as well as field surveys. Data analysis is conducted with the following stages (1) calculation of potential tax receipts, (2) calculating the effectiveness of billboard tax management, 3 analysis of the causes of high low EOL and (4) formulation of policies for the optimization of billboard tax. From the results of the analysis will be formulated the right strategy to minimize EOL. The results showed that the contribution of billboard tax as a source of regional funds is still very small and not yet optimum. This happens because of the high tax on EOL (expected opportunity lost) and the number of wild billboards. The high EOL and wild billboards are due to the relatively weak governance (weak information system, coordination and supervision) and the motivation of the work of officers that has not been optimal. To optimize the potential of tax receipts need to be carried out the development of governance based on integrated information systems. To minimize EOL, a policy of strengthening the governance of The Billboard Tax is necessary: (a) establishing an integrative information system for the management of billboard taxes, (b) reorganization of the billboard tax management organization. (c) improve work rules, (d) improve more effective mechanisms of action, and (e) develop the professionalism of the officers involved.